Epidendrum centroamericanum, a new name for Epidendrum tripetalum (Orchidaceae) - Molinari-Novoa, Eduardo (Phytotaxa, 2016)
Epidendrum tripetalum Hágsater & E.Santiago in Hágsater & Sánchez-Saldaña (2007: t. 997) is a Central American species named after its petal-like labellum. The type comes from the Nicaraguan natural reserve of Cerro Musún, and two paratypes are cited from Belize. However, the epithet is preoccupied within the genus by an obscure Mexican species published by Sessé & Mociño (1894: 205), found in Tenampulco, Puebla. Those species mainly differ by having different inflorescences (opposite to the leaves and one-flowered in the former species; terminal, racemose in the latter), and cannot be assumed to be the same. Therefore, in order to provide an unequivocal name for the recently described species, it is renamed as Epidendrum centroamericanum.